Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1002/(sici)1521-4141(199808)28:08<2265::aid-immu2265>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Lck, Syk and ZAP-70 tyrosine kinases in TCR-mediated phosphorylation of the adapter protein Shc

Abstract: The adapter protein Shc has been implicated in mitogenic signaling via growth factor receptors, antigen receptors and cytokine receptors. Recent studies have suggested that tyrosine phosphorylation of Shc may play a key role in T lymphocyte proliferation via interaction of phosphorylated Shc with downstream molecules involved in activation of Ras and Myc proteins. However, the sites on Shc that are tyrosine phosphorylated in response to TCR engagement and the ability of different T cell tyrosine kinases to pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 46 publications
1
43
1
Order By: Relevance
“…It is interesting to note that phosphorylation of Shc Tyr 317 has been implicated in regulating the specific interaction between Shc and Grap2 (21), which may explain the coregulation of these proteins in our study. Tyr 317 of p52 Shc was reported to be preferred by Lck whereas other sites such as Tyr 239 and Tyr 240 were phosphorylated by Syk and Zap70 in an overexpressed cell line system (22). However, our data showed better correlation between Tyr 317 of Shc and Zap70 as compared with Lck (Figs.…”
Section: Regulation Of Tyrosine Phosphorylation In Adaptor Proteinscontrasting
confidence: 51%
“…It is interesting to note that phosphorylation of Shc Tyr 317 has been implicated in regulating the specific interaction between Shc and Grap2 (21), which may explain the coregulation of these proteins in our study. Tyr 317 of p52 Shc was reported to be preferred by Lck whereas other sites such as Tyr 239 and Tyr 240 were phosphorylated by Syk and Zap70 in an overexpressed cell line system (22). However, our data showed better correlation between Tyr 317 of Shc and Zap70 as compared with Lck (Figs.…”
Section: Regulation Of Tyrosine Phosphorylation In Adaptor Proteinscontrasting
confidence: 51%
“…During in vitro studies, we observed some subtle, but reproducible di erences in phosphorylation of Y239/ 240 versus Y317 by di erent tyrosine kinases (Walk et al, 1998). It is noteworthy that recently, using speci®c Src-family kinase inhibitors, Blake et al (2000) have observed that the Y239/Y240 sites are targets for Src in vivo, while the Y317 is phosphorylated by another kinase, perhaps the PDGF receptor itself.…”
Section: Ch1 Domainmentioning
confidence: 67%
“…Interestingly, both Y239 and Y317 have the canonical +2 asparagine that is critical for the binding of Grb2 ± SH2 domain. We and others have shown that the SH2 domain of Grb2 can bind to both the Y239 and Y317 (Walk et al, 1998). Velazquez et al (2000) recently reported that Grb2 may bind preferentially to Y317, but Grb2 could bind equally well to the Y239 site when the Y240 was also phosphorylated.…”
Section: Ch1 Domainmentioning
confidence: 73%
“…We demonstrate that Ly-GDI associates with the SH2 domain of the adapter protein Shc. Shc is tyrosine-phosphorylated by ZAP-70 upon TCR engagement, and it then forms complexes with Grb2 as well as with other proteins (66). Moreover, Shc was shown to be involved in activation of c-Rel and mitogen-activated protein kinase, and it is required for TCRinduced interleukin-2 production (67).…”
Section: Discussionmentioning
confidence: 99%